Initial effectiveness of an ICBT-protocol for GAD in psychiatric care – A feasibility-pilot study - Vilgot Huhn; Erik Andersson; Tove Wahlund; Erik Forsell (Internet Interventions)
Generalized Anxiety Disorder (GAD) is a common and debilitating anxiety disorder with a chronic course and a low rate of spontaneous remission. Previous internet-delivered treatments for GAD in clinical routine care has been shown to be effective but tend to use a mix of many different treatment components, often based in several theoretical models. Another approach could be to instead develop more focused and theory driven treatments, potentially allowing the protocol to be shorter and less demanding for patients. In this pilot-feasibility-trial we implemented a treatment focusing on one target core construct (intolerance of uncertainty) at the internet psychiatry clinic in Stockholm. The treatment was administered to 22 individuals with GAD. We found a significant reduction in GAD symptoms of similar effect size to previous studies of CBT and ICBT for GAD in routine clinical care. Patients rated overall high levels of treatment satisfaction and treatment credibility. Only two patients dropped out from the treatment. Among the remaining patients a median of 7.5 out of 8 modules were completed. We conclude that the treatment protocol is preliminarily effective, acceptable to patients and clinicians, and feasible to implement in routine psychiatric care.